A Psychometric Study of a Spanish Version of the Negative Acts Questionnaire-Revised: Confirmatory Factor Analysis - Dujo López, Víctor; González Trijueque, David; Graña Gómez, José L.; Andreu Rodríguez, José M. (Frontiers in Psychology, 2020)
Background: The NAQ (Negative Acts Questionnaire) has been widely used in more than 40 countries to measure the mobbing phenomenon. This research aims to present a psychometric study based on the Spanish version of the NAQ-R carried out by González-Trijueque and Graña (2013). As opposed to the original scale, this sample contains 23 items and a three-dimension model (personal bullying, work-related bullying and physically intimidating forms of bullying). Methods: We used a heterogeneous occupational sample of 2,538 Spanish employees to analyze internal consistency and concurrent validity. In addition, a Confirmatory Factor Analysis was carried out based on the GLS (generalized least squares) method. Results showed high internal reliability (Cronbach’s alpha = 0.91) and high correlations containing clinical symptoms, burn-out indicators, and coping resources. The Confirmatory Factor Analysis developed upon the heterogeneous occupational sample validates the three-dimension structure in the Spanish version of the NAQ-R aimed to measure harassment behaviors at the workplace. Conclusions: The NAQ-R reaffirms its validity and reliability as a measure for mobbing-related behaviors. Hence, the scale may become a useful tool in research and forensic practice.